Can ruminant urine-N rate and plants affect nitrate leaching and its isotopic composition?. Issue 1 (2nd January 2020) - Rayner, Sephrah; Clough, Tim J.; Baisden, Troy; Moir, Jim
ABSTRACT: Worldwide there is an increasing awareness of the potential risks that pasture grazing systems pose to freshwater. Excess nutrient levels, predominately nitrate ( N O 3 − ), result in reduced water quality. This study focused on further understanding how the presence or absence of perennial ryegrass ( Lolium perenne L) and bovine urine (BU) influenced both the N O 3 − isotopic signature and the amount of N O 3 − leached. Plant presence resulted in lower N O 3 − -N concentrations and reduced N O 3 − -N leaching over the nine-month trial period. A total of 15, 79 and 234 kg/N/ha was leached from the 0, 300 and 700 kg/N/ha BU treatments, respectively. Drainage volumes varied with season and plant treatments (plants 420±47 mm, no-plants 539±29 mm total drainage). The isotope values were found to be most influenced by plant treatment in the absence of BU. Under BU these isotopic signatures varied temporally due to denitrification and were influenced by plant treatment in the absence of BU, but this does not confound interpretation of isotope data when BU is applied. Nitrate isotopes show potential for identifying N O 3 − sources and soil processes forming and removing N O 3 − . Further datasets are required to improve our understanding of BU rate effects on the temporal dynamics.